CAREER MATURITY LEVELS AMONG HIGH SCHOOL STUDENTS IN CILACAP - Pradana, Tatang Agus; Solikhah, Linda Dwi (Counsenesia Indonesian Journal Of Guidance and Counseling, 2023)
The career choices made by individuals have a significant impact on their overall happiness and well-being. Hence, making accurate and informed career decisions is crucial during the journey of life. The process of career decision-making typically begins during late adolescence or early adulthood, with education playing a vital role in preparing individuals for this important milestone. This quantitative study employed survey techniques and exploratory descriptive analysis using SPSS to examine the career maturity levels of high school students in Cilacap. A career questionnaire was distributed to the participants via Google Forms. The findings revealed that the students exhibited low levels of career maturity attitudes. Further details and discussions on this topic are presented in the manuscript.